Insights Into the Biological Role of NEDD4L E3 Ubiquitin Ligase in Human Cancers - Xie, Shangdan; Xia, Lu; Song, Yizuo; Liu, Hejing; Wang, Zhi-wei; Zhu, Xueqiong (Frontiers in Oncology, 2021)
Neural precursor cell expressed developmentally downregulated 4-like (NEDD4L) is an E3 ubiquitin ligase, which has been reported to participate in multiple cellular procedures by regulation of substrate ubiquitination and subsequent protein degradation. A great number of evidence has demonstrated that NEDD4L mainly functions as a tumor suppressor in most cancer types while it also acts as an oncogene in a few cancers. In this review, we summarize the role of NEDD4L in carcinogenesis and related underlying molecular mechanism to improve our understanding of its importance in tumorigenesis of human malignancies. Developing clinical drugs targeting NEDD4L could be a potential therapeutic strategy for cancer therapy in the future.